Relationship between Serum Interleukin-6 Level and Severity of Acne Vulgaris in Women - Falika, Najwa Luna; Setyawati, Amallia Nuggetsiana; Kusumaningrum, Novi; Damayanti, Galih Sari (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND:  Acne vulgaris is more common in women than men and is observed more frequently in older adolescents than younger adolescents (pre-teens). This is due to higher sebum production, which supports the growth of Propionibacterium acnes. Propionibacterium acnes contributes to initiating and maintaining inflammatory processes induced by immunological reactions. It activates the Toll-like receptor (TLR) 2 and 4 immune systems by releasing interleukin-6 (IL-6) as a core mediator of inflammation. AIMS: This study aims to determine the relationship between serum IL-6 levels and the severity of acne vulgaris in women METHOD: This research employs an analytical observational study design with a cross-sectional approach, involving 15 female subjects diagnosed with acne vulgaris, divided into three groups. The study will occur in Semarang city from July 2024 to September 2024.RESULT:  This study involved 15 female students from Diponegoro University, categorized based on the severity of acne vulgaris (mild, moderate, severe). Blood samples were taken to measure serum IL-6 levels using the ELISA method. The average IL-6 levels found were: mild 1.00 ± 0.55 pg/ml, moderate 1.47 ± 0.27 pg/ml, and severe 1.99 ± 0.42 pg/ml. Analysis revealed a significant relationship between serum IL-6 levels and the severity of acne vulgaris (p = 0.011), supporting the hypothesis of a correlation between the two.CONCLUSION: There is a significant relationship between serum IL-6 levels and the severity of AV in women. There is a meaningful difference in serum IL-6 levels between the mild and severe AV groups.